Trend analysis of temperatures in Shahat area in northeastern part of Libya For the period 1970 -2020 (Journal of Libya for geographical studies, 2024)
The research aims to analyze the change in temperature in Shahat area by analysis monthly seasonal, and annual data for the minimum and maximum temperature to detect positive and negative changes in temperature trends in the study area by employing statistical analysis using Cumulated Sums, T-test, and regression Simple linear analysis. The results of the study indicated the presence of a positive thermal trend in the minimum, maximum and dry temperatures in the Shahat area at a level of statistical significance less than 0.05, consistent with climate changes in the Mediterranean basin area, with trends towards increase in temperature without statistical significance.
Keywords: Trend analysis; Cumulated Sums; simple linear regression; Shahat area; northeastern Libya